Relationship between knowledge level and medication compliance in hypertension patients at Plaju health center, Palembang city: A cross-sectional study - Putri, Anggy Utama; Rosadi, Erik (Indonesian Journal of Health Services, 2025)
Background: Hypertension is a major public health problem that requires long-term treatment and consistent medication adherence to prevent cardiovascular complications. Poor adherence to antihypertensive therapy remains a major challenge in primary health care settings. Objective: This study aimed to analyze the relationship between knowledge level and medication compliance among hypertension patients at Plaju Health Center in Palembang City. Methods: This quantitative study used a cross-sectional design conducted at Plaju Health Center from February to April 2025. The population consisted of 1,659 hypertension patients, and a sample of 94 respondents was determined using the Slovin formula. Respondents were selected using purposive sampling. Data were collected using the Medication Adherence Rating Scale (MARS) questionnaire and a structured knowledge questionnaire that had been tested for validity and reliability. Data analysis included univariate analysis to describe respondent characteristics and bivariate analysis using the Chi-square test to examine the relationship between knowledge level and medication adherence. Results: The results showed that most respondents had good knowledge levels (63.8%) and more than half demonstrated medication adherence (58.5%). Statistical analysis showed a significant relationship between knowledge level and medication compliance among hypertension patients (p = 0.001). Respondents with good knowledge levels were more likely to adhere to antihypertensive medication therapy compared with respondents who had poor knowledge. Conclusion: Knowledge level is significantly associated with medication adherence among hypertension patients. Improving patient knowledge through health education programs may enhance treatment compliance and support better hypertension management in primary health care settings.